Governance Changes through Shareholder Initiatives: The Case of Proxy Access - Bhandari, Tara; Iliev, Peter; Kalodimos, Jonathan (Journal of Financial and Quantitative Analysis, 2021)
Abstract We study a regulatory change that led to over 300 shareholder proposals to instate proxy access and more than 250 firms adopting proxy access from 2012 to 2016. The firms expected to benefit most from proxy access have the most positive market reaction to receiving a proposal, but adoptions are not concentrated at these firms. We find that proposing and voting shareholders do not discriminate between firms that would or would not benefit and that management resists proxy access at the firms that stand to benefit most. This process results in the concentration of adoptions at large, already-well-governed firms.